Influences on viral replication and sensitivity to GLS4, a HAP compound, of naturally occurring T109/V124 mutations in hepatitis B virus core protein. Issue 10 (23rd May 2017) - Wang, Jianghua; Zhang, Haiying; Zhang, Yingjun; Jiang, Dong; Li, Jing; Goldmann, Siegfried; Ren, Qingyun; Fei, Ran; Wang, Xueyan; Wei, Lai
Abstract : Heteroaryldihydropyrimidine (HAP) compounds inhibit HBV replication by binding to a hydrophobic pocket at the interface between hepatitis B virus core protein (HBcAg) dimer, which interrupts capsid assembly by changing the kinetics and thermodynamics during this process. Structure biological studies have identified several amino acids in HBcAg crucial for compound binding. Here, we investigated the polymorphisms of T109 and V124 amino acids in HBV sequences submitted to GenBank database. Naturally occurring T109 and V124 and/or possible compensatory mutations in neighbored amino acids were introduced into HBV‐expressing plasmids. Viral replication competence and sensitivity to GLS4, a HAP compound, were evaluated using transient transfection and in vitro infection cell models. All tested mutations in these amino acids led to decreasing viral DNA replication at different levels. Specially, T109N and all V124 mutants caused severe deficiencies in viral plus‐strand DNA synthesis. T109I single mutation and all T109S/M/C/N mutations impaired HBeAg secretion. T109I showed modestly decreased sensitivities with IC50 3.3‐ to 6.8‐folds higher than wild‐type virus. In vitro infection assay showed T109N and all V124 mutants failed to synthesize cccDNA and following viral proteins. The other mutants, however, produced functional cccDNA pools as wild‐type virus did. Taken together, we profiled the competences of viral replication and sensitivities to capsid inhibitor of naturally existing mutations in T109 and V124. This will help to understand the possible antiviral resistance issues in future clinical applications of capsid inhibitors.